The impact of indoor air pollution on the lung cancer - literature review - Anna Korzeniowska; Anna Kozłowska; Marcela Maksymowicz; Piotr Machowiec; Aleksandra Zimna; Hubert Wróblewski; Ilona Gąbka; Weronika Dalamata; Jan Dąbrowski; Karolina Gendek (Kazimierz Wielki University, 2023)
Introduction: Lung cancer is the most diagnosed type of cancer and the leading cause of death around the world. The most important risk factor for lung cancer is tobacco smoking. However, there are a lot of other lung cancer risk factors, which include: second-hand smoke exposure, environmental exposures (indoor and outdoor air pollution), occupational exposures, genetic predisposition, and previous lung disease. In this study, we would like to present the actual state of knowledge about the influence of radon as well as other indoor air pollutants on the prevalence of lung cancer. State of knowledge: We analyzed nineteen studies in terms of the impact of indoor air pollution on morbidity and mortality caused by lung cancer. The authors of the included studies agree that both radon and other household air pollution (HAP) increase risk of the lung cancer. HAPs are formed during the combustion of solid fuels (i.e. charcoal, wood). Indoor air pollution can cause in the lungs chronic inflammation, cells damage and their proliferation, depletion of antioxidants, impairment of defense mechanisms, production of reactive oxygen species as well as genetic mutations. Radon, on the other hand, emits alpha radiation, which can affect the respiratory epithelium and produce various cytotoxic and genotoxic effects, which promote carcinogenesis. The risk of lung cancer rises by approximately 6-16% per 100 Bq/m3 increase in long-time average residential radon concentration.  Conclusions: Radon and other indoor air pollutants are crucial lung cancer risk factors. It is essential to reduce HAPs production, especially in rural areas, where many people still use coal, wood, or straw for household heating and cooking. Moreover, there are regions where is a need to improve ventilation as well as to switch to clean fuel sources, such as gas and electricity. These activities will contribute to reducing the concentration of HAPs in buildings and decreasing the risk of lung cancer.